2015 Crop Performance in Southeast Kansas - Gretchen Sassenrath; Jane Lingenfelser; L. Mengarelli; X. Lin (Kansas Agricultural Experiment Station Research Reports, 2016)
Crop variety testing determines the production potential of newly released crop cultivars in Southeast Kansas. The genetic potential is moderated by environmental conditions during the growing season as well as soil productive capacity.
Keywords: wheat; corn; soybean; sorghum